Neuroblastoma cell growth and invasiveness is modulated by the activity of N-acetylglucosaminyltransferase-III - Adam P. Burch; M. Kristen Hall; Ruth A. Schwalbe (PLoS ONE, 2026)
The presence of complex N-glycans with β1,6-N-acetylglucosamine (GlcNAc) on cells has long been associated with cancer. For this reason, the role of N-acetylglucosaminyltransferase-III (GnT-III, MGAT3 ) to hinder terminal N-glycan processing by the addition of β1,4-GlcNAc residues (bisected N-glycan), has earned GnT-III a reputation as a tumor suppressor. In this study, by the creation and characterization of human MGAT3 knockout in the Be(2)-C cell line, a NB cell line, ( MGAT3-/- ), we solidify GnT-III activity as a suppressor of NB progression by showing that the loss of GnT-III coincided with increased cell proliferation and cell spheroid invasion, along with cell migration, and cell-cell adhesion, and modified cell types. Lectin blotting results indicated that bisected N-glycans were greatly diminished in MGAT3-/- . Further GNL and L-PHA binding suggested that oligomannose and β1,6-GlcNAc branched N-glycans were raised in MGAT3 -/- relative to the BE(2)-C cell line. Cellular phenotypes of MGAT3-/- could be rescued by transient expression of Mgat3 cDNA. Likewise, altered levels of bisecting GlcNAc N-glycans in a rat NB cell line (NB_1) overexpressing GnT-III had reduced cell-cell adhesion, cell migration, and cell invasiveness. We conclude that lowered GnT-III activity promotes cell invasiveness and growth in NB, and speculate that oligomannose and β1,6-GlcNAc branched N-glycans are key determinants.